Constituição da identidade profissional docente: estudo com professoras alfabetizadoras do município de Cáceres/MT - Nascimento, Renata Cristina de Lacerda Cintra Batista (Universidade do Vale do Rio dos Sinos, 2021)
Identifying, describing and analysing the ways of the constitution of the professional identity of literacy teachers in the city of Cáceres/MT in their professional contexts is the objective and the challenge that this thesis assumes. When considering the professional identity of teachers as an object of investigation, from the Teaching Studies and the post-structuralist perspective, a dialogue with ten teachers interviewed during the covid-19 pandemic is proposed using the WhatsApp application and video connection call. To work with the concept of identity, are used such authors as Zygmunt Bauman, Kathryn Woodward, Stuart Hall, Marcos Pereira, Alfredo Veiga-Neto, among others. Regarding the concept of teaching, support is sought in the researches of Maurice Tardif, Bernardete Gatti, Elba Barreto, Elí Fabris, Maria Cláudia Dal’Igna, among others. Based on these concepts of identity and teaching, it was possible to organize and analyse two major categories involved in the processes of professional identity constitution: (self) teaching responsibility and teacher responsibility. In the first perspective, the teacher assumes expectations and commitments that demand from her beyond what teaching allows her, inflating her daily life with numerous complex social demands in a compensatory movement that ends up resulting in a loss of focus. In the second, she assumes the function of thinking, planning and acting pedagogically to build knowledge. In summary, it is possible to conclude that deepening the studies on the responsibilities assumed by the teachers becomes important to understand the teaching identity today, since the concepts that the teachers formulate regarding their professional identity are involved with the way they teach and the way they position themselves in the face of educational challenges. Thus, they can often deviate from teaching and learning activities to devote themselves to social missions; they can also blame themselves, get sick or give up in the face of bad results.
Keywords: Docência; Identidade; Profissão docente; Professora alfabetizadora; Responsabilidade; Teaching; Identity; Teaching profession; Literacy teacher; Responsibility; ACCNPQ::Ciências Humanas::Educação